2011
DOI: 10.1016/j.sjopt.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of canaloplasty

Abstract: Canaloplasty is a method of lowering intraocular pressure (IOP) by which a flexible, beacon-tipped microcatheter equipped with an ophthalmic viscosurgical device (OVD) delivery system is used to catheterize and introduce a suture into Schlemm's canal. Ligation of this suture provides tension on the canal and facilitates aqueous outflow. Canaloplasty is designed to be a blebless procedure that requires no antifibrotic agents and has been shown to safely and effectively lower IOP in patients with open-angle glau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Canaloplasty is a relatively novel surgical method which aims at restoring the natural pathway of aqueous humour outflow via Schlemm's canal using circumferential viscodilation and a tension suture to permanently distend the trabecular meshwork without inducing a filtering bleb (Godfrey et al 2009;Harvey & Khaimi 2011;Grieshaber 2012;Klink et al 2012). As prospective randomized clinical trials comparing canaloplasty to the current gold standard of trabeculectomy have been lacking and only a limited number of centres are able to offer both techniques, we were compelled to address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canaloplasty is a relatively novel surgical method which aims at restoring the natural pathway of aqueous humour outflow via Schlemm's canal using circumferential viscodilation and a tension suture to permanently distend the trabecular meshwork without inducing a filtering bleb (Godfrey et al 2009;Harvey & Khaimi 2011;Grieshaber 2012;Klink et al 2012). As prospective randomized clinical trials comparing canaloplasty to the current gold standard of trabeculectomy have been lacking and only a limited number of centres are able to offer both techniques, we were compelled to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Severe adverse events and the need for an intensive postoperative treatment regimen have encouraged glaucoma surgeons to develop less invasive nonpenetrating procedures avoiding filtering blebs (Godfrey et al 2009;Francis et al 2011;Grieshaber 2012;Jampel et al 2012;Bettin & Di Matteo 2013;Wallin et al 2013;Yamamoto et al 2013). Canaloplasty is a non-filtering, bleb-free method combining viscocanalostomy with the placement of a 360°i ntracanalicular tension suture within Schlemm's canal, thus allowing aqueous humour outflow through the natural pathway (Godfrey et al 2009;Harvey & Khaimi 2011;Grieshaber 2012). Previous studies comparing non-penetrating with penetrating glaucoma surgeries have reported that although canaloplasty may not be as effective as filtering surgery in lowering IOP without medication, complication rate and risk of serious vision-threatening adverse events are low (Ayyala et al 2011;Brusini & Tosoni 2012;Bruggemann et al 2013;Matlach et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, transient hyphaema was found to be a complication, in the early postoperative period in some cases (9.8 %, 1 day after surgery). Transient hyphaema is the most common post-canaloplasty complication according to the previous peer-reviewed literature, with a reported incidence ranging from 6.1 to 70 % [1]. As in previous series [1], all transient hyphaema resolved within 1 week after surgery.…”
Section: Channelography Outcome and Its Correlation With Iop Decreasementioning
confidence: 53%
“…Canaloplasty is an ab externo Schlemm's canal surgical procedure for lowering intraocular pressure (IOP) in primary open-angle glaucoma (POAG) eyes, utilising a viscocanalostomy surgical dissection to insert a flexible, beacon-tipped microcatheter, equipped with an ophthalmic viscosurgical device (OVD) delivery system, to catheterise, dilate and introduce a tension suture into Schlemm's canal [1,2]. This suture is aimed at providing enough circumferential tension to distend the canal and consequently to increase the aqueous outflow and decrease IOP [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation